Cutting tool
By forming a hexagonal W(C1-aNa)x coating on the cutting tool, especially in titanium alloy turning, the problem of short tool life under high thermal load is solved, and wear resistance and heat resistance are improved.
Patent Information
- Application Number
- CN202380093878.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-17
- Publication Date
- 2025-09-05
AI Technical Summary
Existing cutting tools have a short lifespan in titanium alloy turning, especially in high thermal load environments where wear resistance and heat resistance are insufficient.
The coating includes a first layer composed of hexagonal crystal W(C1-aNa)x, where a is greater than 0.3 and less than 0.8, and x is greater than 0.8 and less than 1.2. The coating may also include a second layer and a third layer, each layer being composed of a specific element compound and formed by physical vapor deposition.
Significantly improves the wear resistance and heat resistance of cutting tools under high thermal loads, extending tool life.
Smart Images

Figure CN120603665A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to cutting tools. Background Art
[0002] Various studies are underway to extend the life of cutting tools. Japanese Patent Application Publication No. 2022-095116 (Patent Document 1) discloses a cutting tool comprising a substrate and a coating disposed on the substrate. The coating includes a first layer composed of metallic tungsten and hexagonal ditungsten carbide.
[0003] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Laid-Open No. 2022-095116 Summary of the Invention
[0004] Problems to be solved by the invention The cutting tool disclosed herein comprises a substrate and a coating disposed on the substrate, wherein: The coating comprises hexagonal W (C 1-a N a ) x The first layer of The a is greater than or equal to 0.3 and less than or equal to 0.8, The x is greater than or equal to 0.8 and less than or equal to 1.2. BRIEF DESCRIPTION OF THE DRAWINGS
[0005] Figure 1 This is a perspective view illustrating one embodiment of a cutting tool.
[0006] Figure 2 This is a schematic enlarged cross-sectional view of an example of the cutting tool according to the first embodiment.
[0007] Figure 3 This is a schematic enlarged cross-sectional view of another example of the cutting tool according to the first embodiment.
[0008] Figure 4 This is a schematic enlarged cross-sectional view of another example of the cutting tool according to the first embodiment. DETAILED DESCRIPTION
[0009] [Problems to be Solved by the Present Disclosure] There is a demand for cutting tools that have a long tool life even in a high thermal load environment such as during turning of titanium alloys.
[0010] Therefore, an object of the present disclosure is to provide a cutting tool having a long tool life, particularly in an environment with a high thermal load such as during turning of titanium alloys.
[0011] [Effects of the Present Disclosure] The cutting tool disclosed herein can have a long tool life even in an environment with a high thermal load, such as during turning of titanium alloy.
[0012] [Description of Embodiments of the Present Disclosure] First, embodiments of the present disclosure will be listed and described.
[0013] (1) The cutting tool disclosed herein comprises a substrate and a coating disposed on the substrate, wherein: The coating comprises hexagonal W (C 1-a N a ) x The first layer of The a is greater than or equal to 0.3 and less than or equal to 0.8, The x is greater than or equal to 0.8 and less than or equal to 1.2.
[0014] The cutting tool disclosed herein can have a long tool life even in an environment with a high thermal load, such as during turning of titanium alloy.
[0015] (2) In the above (1), in the X-ray diffraction spectrum of the first layer, a peak may exist in a range where the diffraction angle 2θ is 46.0° or more and 47.0° or less.
[0016] The peak with a diffraction angle 2θ of 46.0° to 47.0° (hereinafter referred to as the "first peak") originates from the (105) plane of hexagonal tungsten nitride. The presence of the first peak in the X-ray diffraction spectrum of the first layer further improves the heat resistance of the coating.
[0017] (3) In the above (1) or (2), the thickness of the first layer may be 0.3 μm or more and 4.0 μm or less. This further improves the tool life.
[0018] (4) In any of the above (1) to (3), The coating further includes a second layer disposed on a side of the first layer opposite to the substrate. The second layer can be composed of at least one element selected from the first group consisting of elements from Group 4, Group 5, Group VI of the periodic table, aluminum and silicon, or a compound consisting of at least one element selected from the first group and at least one element selected from the second group consisting of carbon, nitrogen, oxygen and boron.
[0019] This further increases tool life.
[0020] (5) In any of the above (1) to (4), The coating further includes a third layer disposed between the substrate and the first layer. The third layer can be composed of at least one element selected from the first group consisting of elements from the fourth group, fifth group, sixth group, aluminum and silicon of the periodic table, or a compound consisting of at least one element selected from the first group and at least one element selected from the second group consisting of carbon, nitrogen, oxygen and boron.
[0021] This further increases tool life.
[0022] (6) In any of the above (1) to (5), The substrate may include at least one selected from the group consisting of cemented carbide, cermet, high-speed steel, ceramic, cubic boron nitride sintered body, and diamond sintered body. Thus, the tool has excellent hardness and strength at high temperatures.
[0023] [Details of the embodiments of the present disclosure] A specific example of a cutting tool according to one embodiment of the present disclosure (hereinafter also referred to as "this embodiment") is described below with reference to the accompanying drawings. In the drawings of this disclosure, identical reference numerals denote identical or equivalent parts. Dimensional relationships, such as length, width, thickness, and depth, are appropriately modified for clarity and simplicity in the drawings and do not necessarily represent actual dimensional relationships.
[0024] In this specification, expressions in the form of "A to B" refer to the upper and lower limits of a range (i.e., greater than A and less than B). When there is no unit recorded in A and only the unit is recorded in B, the unit of A is the same as the unit of B.
[0025] In this specification, when compounds and the like are represented by chemical formulas, unless there is a particular limitation on the atomic ratio, all conventionally known atomic ratios are included, and the atomic ratios are not necessarily limited to those within the stoichiometric range.
[0026] [Implementation 1: Cutting Tool] use Figures 1 to 4 A cutting tool according to an embodiment of the present disclosure will be described.
[0027] like Figure 2 As shown, a cutting tool 10 according to one embodiment of the present disclosure (hereinafter also referred to as “Embodiment 1”) includes a substrate 11 and a coating 14 disposed on the substrate 11, wherein: The coating comprises hexagonal W (C 1-a N a ) x The first layer 12 is composed of The a is greater than or equal to 0.3 and less than or equal to 0.8, The x is greater than or equal to 0.8 and less than or equal to 1.2.
[0028] The cutting tool of this embodiment can have a long tool life even in an environment with a high thermal load, such as during turning of titanium alloys. The reason for this is presumably as follows.
[0029] The first layer is composed of hexagonal W (C 1-a N a ) x Because the first layer contains carbon (C), the friction coefficient at the interface with the workpiece is reduced, reducing cutting resistance. As a result, the wear resistance of the cutting tool containing the first layer is improved, extending the tool life.
[0030] Because the first layer contains nitrogen (N), it has improved heat resistance compared to WC. As a result, cutting tools containing the first layer have improved oxidation resistance and tool life in processes where the cutting edge reaches high temperatures, such as during dry cutting.
[0031] Cutting Tools The cutting tool of this embodiment can be, for example, a drill, an end mill, an indexable cutting insert for a drill, an indexable cutting insert for an end mill, an indexable cutting insert for milling, an indexable cutting insert for turning, a metal saw, a gear cutting tool, a reamer, a tap, etc.
[0032] Figure 1 This is a stereoscopic diagram illustrating one form of a cutting tool. A cutting tool of such a shape is used, for example, as an indexable cutting insert. The cutting tool 10 has a rake face 1, a flank face 2, and a cutting edge ridge portion 3 where the rake face 1 and the flank face 2 intersect. That is, the rake face 1 and the flank face 2 are surfaces connected by clamping the cutting edge ridge portion 3. The cutting edge ridge portion 3 constitutes the front end portion of the blade of the cutting tool 10. The shape of such a cutting tool 10 can also be understood as the shape of the substrate of the cutting tool. That is, the substrate has a rake face, a flank face, and a cutting edge ridge portion connecting the rake face and the flank face.
[0033] <Base material> The substrate of this embodiment can be any substrate as long as it is a conventionally known substrate of this type. For example, the substrate preferably includes at least one selected from the group consisting of cemented carbide (e.g., tungsten carbide (WC)-based cemented carbide, cemented carbide containing Co in addition to WC, cemented carbide to which carbonitrides such as Cr, Ti, Ta, and Nb are added in addition to WC), cermets (cermets primarily composed of TiC, TiN, TiCN, etc.), high-speed steel, ceramics (titanium carbide, silicon carbide, silicon nitride, aluminum nitride, aluminum oxide, etc.), cubic boron nitride sintered compacts (cBN sintered compacts), and diamond sintered compacts. More preferably, the substrate includes at least one selected from the group consisting of cemented carbide, cermets, and cBN sintered compacts.
[0034] In addition, when cemented carbide is used as the substrate, even if such cemented carbide contains an abnormal phase called free carbon or η phase in the structure, the effect of the present embodiment is also shown. In addition, even if the substrate used in the present embodiment is a substrate after surface modification, it does not matter. For example, in the case of cemented carbide, a β-layer can be formed on its surface, or in the case of cermet, a surface solidified layer can be formed. Even if the surface is modified like this, the effect of the present embodiment is also shown.
[0035] When the cutting tool is an indexable cutting insert (such as an indexable cutting insert for milling), the base material may include a base material with a chip breaker or a base material without a chip breaker. The shape of the ridgeline portion of the cutting edge may include a sharp edge (the ridge where the rake and flank faces intersect), a honed shape (a shape that rounds the sharp edge), a negative land (a shape that is chamfered), or a combination of a honed and negative land shape.
[0036] <Lamination> The "coating" involved in this embodiment has the effect of improving various characteristics of the cutting tool, such as defect resistance and wear resistance, by covering at least a portion of the substrate (for example, the cutting-related portion that contacts the workpiece during cutting). The coating can cover at least the cutting-related portion. The coating can also cover the entire surface of the substrate. Even if the composition of the coating is partially different, it does not deviate from the scope of this embodiment. The cutting-related portion of the substrate refers to, for example, an area within 50 μm from the edge line of the blade tip on the surface of the substrate. The coating can also cover the entire surface of the cutting-related portion of the substrate. As long as the effect of the cutting tool disclosed herein is not impaired, even if a coating is not formed on a part of the cutting-related portion of the substrate, it does not deviate from the scope of this embodiment.
[0037] The coating consists of hexagonal W (C 1-a N a ) x The first layer of composition. Figure 2: is a schematic cross-sectional view of a cutting tool in one embodiment of the present invention. Figure 2 As shown, the first layer 12 may also be disposed directly above the substrate 11 .
[0038] The coating can include other layers in addition to the first layer 12. Examples of other layers include Figure 4 The third layer 15 is arranged between the substrate 11 and the first layer 12, and Figure 3 as well as Figure 4 As shown, the second layer 13 is provided on the side of the first layer 12 opposite to the substrate 11, and so on.
[0039] The thickness of the coating can be from 0.3 μm to 10 μm, from 0.5 μm to 10 μm, from 1 μm to 6 μm, or from 1.5 μm to 4 μm. If the coating thickness is less than 0.1 μm, wear resistance tends to decrease. If the coating thickness exceeds 10 μm, the coating tends to peel off or break frequently when high stress is applied between the coating and the substrate, for example, during intermittent processing.
[0040] In this specification, the thickness of the coating refers to the sum of the thicknesses of the layers comprising the coating (first, second, and third layers, etc., described below). The coating thickness is measured using a transmission electron microscope (TEM) by measuring three arbitrary points on a cross-section sample parallel to the normal to the substrate surface and taking the average of the thicknesses measured at these three points. An example of a transmission electron microscope is the "JEM-2100F (trademark)" spherical aberration correction system manufactured by JEOL Ltd. The thicknesses of the layers described below are measured using the same method unless otherwise specified.
[0041] <First Floor> The coating consists of hexagonal W (C 1-a N a ) x (Here, a is 0.3 to 0.8, and x is 0.8 to 1.2.) The first layer is composed of hexagonal W (C 1-a N a ) x It refers to the W (C 1-a N a ) x By making the crystal structure of the first layer hexagonal, the diffusion reaction between the coating and the workpiece is suppressed, reducing adhesion to the workpiece and improving tool life. The first layer can improve the heat resistance, oxidation resistance, and wear resistance of the coating.
[0042] The first layer may be formed of hexagonal W (C 1-a N a ) x The first layer may contain inevitable impurities. Examples of such inevitable impurities include iron (Fe), calcium (Ca), zinc (Zn), sodium (Na), fluorine (F), nickel (Ni), molybdenum (Mo), and chromium (Cr). The content of such inevitable impurities is preferably 0% by mass or more and 0.2% by mass or less relative to the total mass of the first layer. The content of inevitable impurities is measured by glow discharge mass spectrometry. Similarly, the "second layer" and "third layer" described below may also contain inevitable impurities within a range that does not impair the effects of the cutting tool disclosed herein.
[0043] <Crystal structure of the first layer> The first layer is composed of W (C 1-a N a ) x This can be confirmed by XRD analysis. Specifically, by irradiating X-rays onto the surface of each sample on the side opposite to the substrate, X-ray diffraction measurement (XRD measurement) is performed on an arbitrary region of the first layer and analyzed. In the obtained XRD spectrum, both the peaks shown in JCPDS (ICDD) card 01-076-7103 and the peaks shown in 01-77-2001 are observed, and both the peaks shown in JCPDS (ICDD) card 01-075-1012 and the peaks shown in 00-042-0853 are not observed, it is confirmed that the first layer is composed of W (C) having a hexagonal crystal structure. 1-a N a ) x constitute.
[0044] When the coating includes other layers besides the first layer, such as a second layer, a third layer, or an intermediate layer, peaks originating from layers other than the first layer or the substrate (hereinafter also referred to as "other peaks") may be detected in the XRD spectrum. In this case, the peak originating from the first layer is identified using the following method.
[0045] By irradiating the surface of the measurement sample on the side opposite to the substrate with X-rays, the coating is subjected to XRD measurement to obtain a diffraction pattern A. The layer of the measurement sample that is closer to the surface side (X-ray irradiation side) than the first layer is mechanically removed to expose the first layer. By irradiating the surface of the exposed first layer with X-rays, the first layer is subjected to XRD measurement to obtain a diffraction pattern B. The first layer of the measurement sample is mechanically removed to expose the layer that is closer to the substrate side than the first layer. By irradiating the surface of the exposed layer with X-rays, the exposed layer is subjected to XRD measurement to obtain a diffraction pattern C. By comparing diffraction pattern A, diffraction pattern B, and diffraction pattern C, the peak originating from the first layer is identified. In the present disclosure, the X-ray diffraction spectrum in which the peak originating from the first layer is identified by the above steps is referred to as the "X-ray diffraction spectrum of the first layer."
[0046] Examples of an apparatus used for the X-ray diffraction measurement include “SmartLab” (trade name) manufactured by Rigaku Corporation and “X'pert” (trade name) manufactured by Panalytical.
[0047] In this specification, the conditions for XRD measurement are as follows.
[0048] (XRD measurement conditions) Scan axis: 2θ-θ X-ray source: Cu-Kα line (1.541862Å) Detector: 0-dimensional detector (scintillation counter) Tube voltage: 45kV Tube current: 40mA Incident optical system: Utilization of reflective mirrors Light-receiving optical system: Utilization of the analyzer crystal (PW3098 / 27) Step size: 0.03° Cumulative time: 2 seconds Scanning range (2θ): 10°~120° The X-ray diffraction spectrum of the first layer may contain a peak within the range of a diffraction angle 2θ of 46.0° to 47.0°. This peak within the range of a diffraction angle 2θ of 46.0° to 47.0° (hereinafter referred to as the "first peak") is derived from hexagonal tungsten nitride. The presence of the first peak in the X-ray diffraction spectrum of the first layer, i.e., the first layer contains hexagonal tungsten nitride, suppresses diffusion between the coating and the workpiece, further improving the heat resistance of the coating.
[0049] Furthermore, it was confirmed that, as long as the above analysis is performed on the same sample within the range measured by the applicant, there is almost no deviation in the analysis results even if the measurement area is changed and the analysis is performed multiple times. Even if the measurement area is arbitrarily set, there is no random change.
[0050] <Composition of the first layer> The first layer is composed of hexagonal W (C 1-a N a ) x The structure is such that a is greater than or equal to 0.3 and less than or equal to 0.8, and x is greater than or equal to 0.8 and less than or equal to 1.2.
[0051] The lower limit of a is 0.3 or more, and may be 0.4 or more, or 0.5 or more. The upper limit of a is 0.8 or less, and may be 0.7 or less, or 0.6 or less. a may be 0.4 or more and 0.7 or less, or 0.5 or more and 0.6 or less.
[0052] The lower limit of x is 0.8 or greater, and may be 0.9 or greater. The upper limit of x is 1.2 or less, and may be 1.1 or less. x may be 0.9 or greater and 1.1 or less, and may be 1.0.
[0053] In this disclosure, “the first layer is composed of hexagonal W (C 1-a N a ) x "Constituted" means that the first layer can be formed in W(C 1-a N a ) x In addition to the above, the first unit layer 12 may contain inevitable impurities. Examples of inevitable impurities include oxygen and carbon. The overall content of inevitable impurities in the first unit layer 12 may be greater than 0 atomic % and less than 1 atomic %. In this disclosure, "atomic %" refers to the ratio (%) of the number of atoms to the total number of atoms constituting the layer.
[0054] The above-mentioned a is measured using electron energy loss spectroscopy (TEM-EELS). The specific measurement method is as follows.
[0055] The cutting tool was cut along the normal to the coating surface using an argon ion cutter to produce slices with a thickness of 3 to 100 nm, including the cross-section of the coating. The slices were observed at 100,000 to 1,000,000 magnification using a transmission electron microscope (TEM, trade name: "JEM-2100F / Cs," manufactured by JEOL Ltd.), to obtain cross-sectional transmission images of the coating. Electron energy loss spectroscopy (EELS) was applied to the cross-sectional transmission images, scanning at observation points of 10 nm square to observe the energy loss curve associated with the excitation of carbon and nitrogen electrons. In the energy loss curve, the parallel intensity at 270 to 280 eV for carbon and 385 to 395 eV for nitrogen was defined as the background intensity, and the ratio of the carbon energy to the nitrogen energy was calculated. This method can be used to obtain the above-mentioned value a.
[0056] In the present disclosure, the composition W (C1-a N a ) x The total number of C and N atoms is A N1 Atomic number A relative to W M1 Ratio A N1 / A M1 0.8 or more and 1.2 or less. N1 / A M1 It can be measured by Rutherford backscattering (RBS) method. N1 / A M1 If it is within the above range, the effects of the present disclosure will not be impaired.
[0057] <Average thickness of the first layer> The lower limit of the thickness of the above-mentioned first layer can be set to 0.2 μm or more. Thus, the diffusion reaction between the first layer and the cut workpiece is suppressed. The lower limit of the thickness of the first layer can be 0.3 μm or more, 0.5 μm or more, 0.7 μm or more, or 0.9 μm or more. The upper limit of the thickness of the first layer can be 5.0 μm or less. Thus, the coating has high hardness and good wear resistance. The upper limit of the thickness of the first layer can be 4.0 μm or less, 2.0 μm or less, or 1.5 μm or less. The thickness of the first layer can be 0.2 μm or more and 5.0 μm or less, 0.3 μm or more and 4.0 μm or less, 0.5 μm or more and 2.0 μm or less, or 0.7 μm or more and 1.5 μm or less.
[0058] <Second Floor> like Figure 3 as well as Figure 4 As shown, the coating 14 can further include a second layer 13 disposed on the side of the first layer 12 opposite the substrate 11. Here, "disposed on the side of the first layer opposite the substrate" simply means that the second layer 13 is disposed above the first layer 12 (the side away from the substrate). The first and second layers 12, 13 do not need to be in contact with each other. In other words, another layer may be disposed between the first and second layers 12, 13. The second layer 13 may also be disposed directly above the first layer 12. The second layer 13 may also be the outermost layer.
[0059] The second layer can be composed of at least one element selected from the first group consisting of Group IV elements, Group V elements, Group VI elements, aluminum (Al), and silicon (Si), or a compound composed of at least one element selected from the first group and at least one element selected from the second group consisting of carbon (C), nitrogen (N), oxygen (O), and boron (B). Examples of Group IV elements include titanium (Ti), zirconium (Zr), and hafnium (Hf). Examples of Group V elements include vanadium (V), niobium (Nb), and tantalum (Ta). Examples of Group VI elements include chromium (Cr), molybdenum (Mo), and tungsten (W). The second layer can contain impurities in addition to the at least one element selected from the first group or the aforementioned compound, as long as they do not impair the effects of the present disclosure.
[0060] The second layer can be composed of at least one element selected from Group 1A consisting of Cr, Al, Ti, and Si, or a compound consisting of at least one element selected from Group 1A and at least one element selected from Group 2 consisting of carbon, nitrogen, oxygen, and boron.
[0061] Examples of the compound constituting the second layer include AlTiBN, TiAlN, TiAlON, Al2O3, TiAlSiN, TiCrSiN, TiAlCrSiN, AlCrN, AlCrO, AlCrON, AlCrSiN, AlCrBN, TiZrN, TiAlMoN, TiAlNbN, TiSiN, AlCrTaN, AlVN, AlTiVN, TiB2, TiCrHfN, CrSiWN, TiAlCN, TiSiCN, AlZrON, AlCrCN, AlHfN, CrSiBON, TiAlWN, AlCrMoCN, TiCN, TiCON, ZrN, and ZrCN. These compounds can reduce the friction coefficient of the coating and extend the life of the cutting tool.
[0062] The thickness of the second layer may be 0.1 μm or greater. When the second layer is 0.1 μm or greater, the lubricity imparted by the second layer is more readily achieved. While there is no particular upper limit on the thickness of the second layer, a thickness exceeding 2 μm tends to hinder further improvement in the aforementioned lubricity imparting effect. Therefore, considering cost, the thickness of the second layer may be 2 μm or less.
[0063] <Third Floor> like Figure 4 As shown, the coating 14 can further include a third layer 15 disposed between the substrate 11 and the first layer 12. This can improve the adhesion between the substrate 11 and the coating 14.
[0064] The third layer can be composed of at least one element selected from the first group consisting of Group IV elements, Group V elements, Group VI elements, aluminum (Al), and silicon (Si), or a compound composed of at least one element selected from the first group and at least one element selected from the second group consisting of carbon (C), nitrogen (N), oxygen (O), and boron (B). Examples of Group IV elements include titanium (Ti), zirconium (Zr), and hafnium (Hf). Examples of Group V elements include vanadium (V), niobium (Nb), and tantalum (Ta). Examples of Group VI elements include chromium (Cr), molybdenum (Mo), and tungsten (W). The third layer can contain impurities in addition to the at least one element selected from the first group or the aforementioned compound, as long as they do not impair the effects of the present disclosure.
[0065] The third layer can be composed of at least one element selected from Group 1A consisting of Cr, Al, Ti, and Si, or a compound consisting of at least one element selected from Group 1A and at least one element selected from Group 2 consisting of carbon, nitrogen, oxygen, and boron.
[0066] As the compound constituting the third layer, for example, TiWCN, TiN, TiAlN, TiAlON, Al2O3, TiAlSiN, TiCrSiN, TiAlCrSiN, AlCrN, AlCrO, AlCrON, AlCrSiN, AlCrBN, TiZrN, TiAlMoN, TiAlNbN, TiSiN, AlCrTaN, AlVN, AlTiVN, TiB2, TiCrHfN, CrSiWN, TiAlCN, TiSiCN, AlZrON, AlCrCN, AlHfN, CrSiBON, TiAlWN, AlCrMoCN, TiCN, TiCON, ZrN and ZrCN can be listed.
[0067] The thickness of the third layer is not particularly limited within a range that does not impair the effects of this embodiment, and can be, for example, 0.1 μm or more and 2 μm or less.
[0068] <Middle layer> The coating may include an intermediate layer disposed between the second layer and the first layer or between the first layer and the third layer. Examples of the intermediate layer include TiAlCeN, AlTiN, AlTiBN, AlTiSiN, AlTiYN, and AlTiLaN. The thickness of the intermediate layer may be 0.1 μm to 2 μm, 0.3 μm to 1.5 μm, or 0.4 μm to 1.0 μm.
[0069] [Embodiment 2: Method for Manufacturing Cutting Tool] The following describes an example of a method for manufacturing a cutting tool according to Embodiment 1. The method for manufacturing a cutting tool according to this embodiment includes a first step of preparing a substrate and a second step of forming a coating on the substrate. The second step includes forming a first layer. Each step is described below.
[0070] <First Step> In the first step, a substrate is prepared. As the substrate, the substrate described in Embodiment 1 can be used.
[0071] When using cemented carbide as the substrate, a commercially available substrate can be used, or it can be manufactured using conventional powder metallurgy. When manufactured using conventional powder metallurgy, WC powder and Co powder can be mixed using a ball mill or the like to obtain a mixed powder. After drying the mixed powder, it is formed into a predetermined shape to obtain a formed body. This formed body is further sintered to obtain a WC-Co cemented carbide (sintered body). Subsequently, the sintered body is subjected to predetermined tool tip processing, such as honing, to produce a substrate composed of WC-Co cemented carbide. Any substrate other than the above-mentioned can be prepared, as long as it is a conventionally known substrate of this type.
[0072] <Second step> In the second step, a coating is formed on the substrate. The second step includes forming the first layer. Examples of methods for forming the first layer include physical vapor deposition (PVD).
[0073] Examples of physical vapor deposition methods include sputtering, ion plating, arc ion plating, and electron ion beam deposition. In particular, cathode arc ion plating or sputtering, which have a high ion rate of the raw material element, is preferred because the substrate surface can be bombarded with metal or gas ions before the film is formed, significantly improving the adhesion between the film and the substrate.
[0074] When forming the first layer using arc ion plating, the following conditions can be used, for example. First, a WC target (e.g., a sintered target composed of binderless WC containing 93% or more WC by mass and a carbon content of 3 to 6.1% by mass) is placed in two opposing arc evaporation sources within an apparatus. The substrate temperature is set to 400 to 550°C, and the pressure within the apparatus is set to 1.5 to 5.5 Pa.
[0075] As the gas, only nitrogen (N 2 ) gas or a mixed gas of nitrogen gas and argon gas is introduced.
[0076] While maintaining a (negative) bias voltage of 10 to 150 V across the substrate, and using DC or pulsed DC (frequency 20 to 50 kHz), an arc current of 80 to 150 A is supplied to the cathode electrode, generating metal ions from the arc evaporation source, thereby forming the first layer on the substrate. During film formation, the tungsten filament also discharges (emission current 30 to 45 A). This increases the number of ions in the plasma. An example of an apparatus used for arc ion plating is the AIP (trade name) manufactured by Kobe Steel, Ltd. During film formation, the substrate temperature, gas pressure, bias voltage, frequency, arc current, and emission current are maintained constant within the aforementioned ranges.
[0077] By forming a film under the above conditions, a hexagonal W (C 1-a N a ) x (Here, a is greater than or equal to 0.3 and less than or equal to 0.8, and x is greater than or equal to 0.8 and less than or equal to 1.2.) The above conditions are newly discovered by the inventors of the present invention after in-depth research. By adjusting the gas composition, gas pressure, arc current, and bias voltage within the above ranges, it is possible to adjust the composition of the first layer and the presence or absence of the first peak (the peak with a diffraction angle 2θ in the range of greater than or equal to 46.0° and less than or equal to 47.0°) in the XRD spectrum of the first layer. For example, when the amount of nitrogen in the gas is large and the bias voltage is high, there is a tendency for the ratio of carbon (C) in the coating to decrease. In addition, when the gas pressure is low and the partial pressure of nitrogen is low, there is a tendency for the first peak to not exist.
[0078] The second step can include a surface treatment step of the coating such as grinding or shot blasting in addition to the step of forming the first layer. Furthermore, the second step can include steps of forming other layers such as the second layer, the third layer, and the intermediate layer. The other layers can be formed by conventionally known chemical vapor deposition methods or physical vapor deposition methods. From the perspective of being able to form the other layers continuously with the first layer in a single physical vapor deposition apparatus, the other layers are preferably formed by physical vapor deposition.
[0079] Example Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to these Examples.
[0080] Manufacturing of Cutting Tools [Samples 1 to 22, Samples 101 to 105] <First Step> In the first step, a JIS K10 hard material (shape: JIS CNMG120408) was prepared as a substrate, and then the substrate was placed at a predetermined position in an arc ion plating apparatus (manufactured by Kobe Steel, Ltd., trade name: AIP).
[0081] <Second step> In the second step, a coating comprising the first layer was formed on the substrate using arc ion plating to obtain cutting tools for each sample. The first layer was formed using the following method. First, WC targets (sintered targets composed of binderless WC containing at least 93% WC by mass and a carbon content of 3 to 6.1% by mass) were placed in two opposing arc evaporation sources within the apparatus. The substrate temperature was set to 400 to 550°C, and the pressure within the apparatus was set to 1.5 to 5.5 Pa.
[0082] As the gas, only nitrogen (N 2 ) gas or a mixed gas of nitrogen gas and argon gas was introduced.
[0083] In Samples 1 through 22, while maintaining a substrate (negative) bias voltage of 10 to 150 V, and applying DC or pulsed DC (frequency 20 to 50 kHz), an arc current of 80 to 150 A was supplied to the cathode electrode, generating metal ions from the arc evaporation source, thereby forming the first layer on the substrate. During film formation, a tungsten filament discharge (emission current 30 to 45 A) was also performed. During film formation, the substrate temperature, gas pressure, bias voltage, frequency, and emission current were kept constant within the aforementioned ranges. For each sample, the composition of the first layer and the presence or absence of the first peak (a peak with a diffraction angle 2θ of 46.0° to 47.0°) in the XRD spectrum of the first layer were adjusted by adjusting the gas composition, gas pressure, arc current, and bias voltage within the aforementioned ranges.
[0084] In sample 20, a third layer is provided between the substrate and the first layer. The third layer is formed directly above the substrate by the following steps before the first layer is formed. A target (sintered target) containing the metal composition listed in the composition column of the third layer in Table 1 is placed in an arc evaporation source of an arc ion plating device. Next, the substrate temperature is set to 600°C, and the gas pressure in the device is set to 3.5 Pa. A mixed gas of nitrogen, methane, and argon is introduced as a reaction gas. Thereafter, an arc current of 130 A is supplied to the cathode electrode. Metal ions and the like are generated from the arc evaporation source by the supply of arc current, and the third layer is formed to the thickness listed in Table 1.
[0085] In sample 19, a second layer is provided on top of the first layer. After the first layer is formed, the second layer is formed directly above the first layer by the following steps. A target (sintered target) containing the metal composition listed in the second layer composition column in Table 1 is placed in an arc evaporation source of an arc ion plating device. Next, the substrate temperature is set to 550°C, and the gas pressure in the device is set to 4.0 Pa. Nitrogen is introduced as a reaction gas. Thereafter, an arc current of 150 A is supplied to the cathode electrode. Metal ions and the like are generated from the arc evaporation source by the supply of arc current, and the second layer is formed to the thickness listed in Table 1.
[0086] In sample 101, the gas pressure was set to 1.0 Pa, a mixed gas of nitrogen and argon was introduced, the bias voltage was set to 100 V, and the other conditions were the same as those of samples 1 to 22, and film formation was performed.
[0087] In Samples 102 and 103, the gas pressure was set to 1.0 Pa, only nitrogen gas was introduced, and the arc current and bias voltage were changed to make the hexagonal W (C 1-a N a ) a and x in x became the values described in Table 1, and the other conditions were the same as those of Samples 1 to 22, and the films were formed.
[0088] In sample 104, the gas pressure was set to 4.0 Pa, a mixed gas of nitrogen and argon was introduced, the bias voltage was set to 200 V, the arc current was set to 150 A, and other conditions were the same as those of samples 1 to 22, and film formation was performed.
[0089] In Sample 105, the gas pressure was set to 5.0 Pa, a mixed gas of nitrogen and argon was introduced, the bias voltage was set to 500 V, the arc current was set to 190 A, and other conditions were the same as those of Samples 1 to 22 to form a film.
[0090] [Sample 106] The same base material as that of Sample 1 was prepared, and a coating was formed on the base material by the same method as that of Sample 15 of Patent Document 1 to obtain a cutting tool of Sample 106.
[0091] 《Characteristics Evaluation of Cutting Tools》 The cutting tools of each sample were evaluated for the crystal structure of the first layer, the presence or absence of the first peak, the composition of the first layer, and the thickness of each layer.
[0092] <Crystal structure of the first layer and presence of the first peak> The crystal structure of the first layer of each sample was determined by XRD. The specific measurement method has been described in Embodiment 1, so its description will not be repeated. The results are shown in the "Crystal Structure" column of "First Layer" in Table 1.
[0093] The expression "hexagonal" in the "Crystal Structure" column indicates that the first layer does not contain tungsten carbide and tungsten nitride composed of a cubic crystal structure, and that the first layer is composed of hexagonal W (C 1-a N a ) x constitute.
[0094] The expression "Hexagonal + Cubic" in the "Crystal Structure" column indicates that the first layer contains a mixture of hexagonal tungsten nitride (hexagonal WN), hexagonal tungsten carbide (hexagonal WC), and at least one of cubic WN and W3C. If at least one of the peaks indicated by JCPDS (ICDD) cards 01-075-1012 (WN) and 00-042-0853 (W3C) is observed in the XRD spectrum of the first layer, the first layer has a cubic crystal structure.
[0095] "W+hW2C" in the "Crystal Structure" column of Sample 106 means that the first layer is composed of metallic tungsten and hexagonal tungsten carbide.
[0096] In the X-ray diffraction spectrum of the first layer obtained from each sample, the presence or absence of a peak within the diffraction angle 2θ range of 46.0° to 47.0° was confirmed. The results are shown in the "XRD Spectrum First Peak" column under "First Layer" in Table 1. "Present" indicates the presence of the first peak, and "Absent" indicates the absence of the first peak.
[0097] <Composition of the first, second, and third layers> The composition of the first layer of each sample was measured using electron energy loss spectroscopy (TEM-EELS) and Rutherford backscattering (RBS). When the second and third layers were formed, their compositions were also measured. The specific measurement method has been described in Implementation Example 1, so its description will not be repeated. The results are shown in Table 1 under "First Layer (W (C 1-a N a ) x )”, the “a” and “x” columns of the “Second Layer”, and the “Composition” column of the “Third Layer”.
[0098] <Thickness of each layer> The thicknesses of the first, second, and third layers, as well as the coating, were measured using a transmission electron microscope (TEM) (JEOL Ltd., trade name: JEM-2100F). The specific measurement method has been described in Embodiment 1 and will not be repeated here. The results are shown in the "Thickness" column for each layer in Table 1.
[0099] In Table 1, the notation “-” in “Second layer” and “Third layer” indicates that the corresponding layer does not exist in the coating film.
[0100] [Table 1]
[0101] Cutting Test The cutting time (tool life) until the cutting tool was chipped or the flank wear reached 0.15 mm was measured using the cutting tools of each sample under the following cutting conditions. The results are shown in the "Tool Life" column of "Cutting Test" in Table 2.
[0102] Cutting conditions Cutting material: Ti-6Al-4V Speed: V70m / min Feed rate: 0.2mm / rev Cutting depth: 1mm The above-mentioned cutting conditions correspond to turning of titanium alloy, and a high thermal load is applied to the cutting tool during machining.
[0103] [Table 2]
[0104] The cutting tools of Samples 1 to 22 correspond to the examples, and the cutting tools of Samples 101 to 106 correspond to the comparative examples. The cutting test results confirmed that the cutting tools of Samples 1 to 22 had longer tool life than the cutting tools of Samples 101 to 106, even under high heat load environments.
[0105] As described above, the embodiments and examples of the present disclosure have been described. However, it is anticipated from the outset that the configurations of the above-described embodiments and examples may be appropriately combined.
[0106] The embodiments and examples disclosed herein are to be considered in all respects as illustrative and non-restrictive. The scope of the present invention is indicated not by the embodiments and examples described above but by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0107] Description of reference numerals: 1: Rake face; 2: Flank face; 3: Blade edge; 10: Cutting tool; 11: Base material; 12: First layer; 13: Second layer; 14: Coating; 15: Third layer.
Claims
1. A cutting tool comprising a substrate and a coating disposed on the substrate, wherein: The coating comprises hexagonal W (C 1-a N a ) x The first layer of The a is greater than or equal to 0.3 and less than or equal to 0.8, The x is greater than or equal to 0.8 and less than or equal to 1.
2.
2. The cutting tool according to claim 1, wherein In the X-ray diffraction spectrum of the first layer, a peak exists within a range where the diffraction angle 2θ is 46.0° or more and 47.0° or less.
3. The cutting tool according to claim 1 or 2, wherein: The average thickness of the first layer is 0.3 μm or more and 4.0 μm or less.
4. The cutting tool according to any one of claims 1 to 3, wherein The coating further includes a second layer disposed on a side of the first layer opposite to the substrate. The second layer is composed of at least one element selected from the first group consisting of elements of Group 4, Group 5, Group VI of the periodic table, aluminum and silicon, or a compound composed of at least one element selected from the first group and at least one element selected from the second group consisting of carbon, nitrogen, oxygen and boron.
5. The cutting tool according to any one of claims 1 to 4, wherein The coating further includes a third layer disposed between the substrate and the first layer. The third layer is composed of at least one element selected from the first group consisting of elements of Group 4, Group 5, Group VI of the periodic table, aluminum and silicon, or a compound composed of at least one element selected from the first group and at least one element selected from the second group consisting of carbon, nitrogen, oxygen and boron.
6. The cutting tool according to any one of claims 1 to 5, wherein The substrate includes at least one selected from the group consisting of cemented carbide, cermet, high-speed steel, ceramic, cubic boron nitride sintered body, and diamond sintered body.
Citation Information
Patent Citations
Cutting tool
JP2022095116A